Seroprevalence of HSV-2 in multiple subgroups of infertile men with abnormal sperm parameters and those seeking sex selection: a case-control study - Mohamad Javad Mahmodi; Somayeh Shatizadeh Malekshahi; Haleh Soltanghoraee (BMC Infectious Diseases)
Abstract Background Herpes simplex virus type 2 (HSV-2) is a common sexually transmitted infection (STI) primarily acquired through sexual contact. In 2000, the World Health Organization (WHO) for the first time reported the association of STIs with male infertility. Infertility is described as the inability to achieve a clinical pregnancy after engaging in regular, unprotected sexual intercourse for a year or more. HSV-2 infection is a significant concern for infertility, with evidence suggesting it can contribute to a range of reproductive complications. The seroprevalence of HSV-2 among infertile men in Iran has not yet been determined. Therefore, we conducted a case-control study to examine the seroprevalence of HSV-2 in multiple subgroups of infertile men with abnormal sperm parameters (Case) and individuals seeking sex selection services and those with normal sperm parameters (Control). Method Blood samples were collected from infertile males seeking fertility treatment, and those seeking sex selection at the Avicenna Infertility Clinic in Tehran, Iran between July 2023 and February 2024. Demographic and clinical data were collected through a questionnaire. Anti-HSV-2 IgG antibodies (Abs) were detected using a commercially available ELISA kit [Herpes simplex 2 (gG2 purified), Vircell, Spain]. Results Of the 486 samples that met the eligibility criteria, 420 were tested. The ELISA testing was performed on 98 control, 32 Teratozoospermia (T), 45 Asthenozoospermia (A), 48 Oligoteratozoospermia (OTA), 50 Azoospermia (Azo), and 147 Teratozooasthenospermia (TA) samples. Thirteen samples came out positive for HSV-2 IgG Abs (3.41% case and 2.04% control group). Of these 13 positive samples, 7 were from the TA group, 2 from the T group, 2 from the Azo group, and 2 control. The age (43.15 ± 5.10 vs. 37.74 ± 6.20, p = 0·0020) and marriage duration (12.54 ± 6.88 vs. 8.12 ± 4.95, p = 0·0019) were significantly higher in the HSV-2 IgG Ab positive group. Conclusion The results of this study enhance our understanding of the epidemiology of HSV-2 in individuals seeking infertility treatment. It can be inferred that the seroprevalence of HSV-2 IgG among patients referring to an infertility treatment clinic in Tehran is relatively low. The study also indicates that the chance of HSV-2 infection increases with age. The highest number of positive cases in the TA suggests that HSV-2 may adversely affect sperm motility and morphology.